Seismic cross-hole tomography in modeling ISC'2 experimental site - J. M. Carvalho (2008)
The extensive in-situ investigation and characterization of ISC2 experimental site, located on the campus of the Faculty of Engineering of the University of Porto (FEUP), comprised a geological reconnaissance of the area as well as the application of several geophysical and geotechnical surface and borehole methods, namely seismic P- and S-wave seismic refraction, conventional and tomographic cross-hole, high resolution SH-wave shallow reflection, geoelectrical resistivity imaging, penetration tests and pressure-dilatometer tests. In parallel, a laboratory testing program was carried out on undisturbed samples, including triaxial tests with bender elements and resonant column tests. Broadly, the site is geologically formed by an upper layer of soil with varying thickness, overlaying rather weathered granite (saprolite) contacting an older gneissic migmatite having dominant sub-vertical foliation, with the piezometric water level at a depth about 10m during the surveying period. Direct and indirect results from some of the referred geophysical surveys, namely those obtained from seismic refraction and reflection, conventional cross-hole, down-hole, geoelectrical imaging and ground penetrating radar, as well as from the geotechnical in-situ and laboratory tests, have been previously presented, compared and discussed. Following a brief summary of some relevant contextualizing issues, the present report presents and discusses results obtained from the conducted seismic cross-hole tomography survey as well as their integration in the previously obtained tentative ISC2 experimental soil profile interpretation model.